PENGARUH PERSEPSI MANFAAT PAJAK, SOSIALISASI PERPAJAKAN, MORAL-ETIKA PAJAK, DAN PENGETAHUAN TENTANG PERPAJAKAN TERHADAP PERILAKU TAX AVOIDANCE TERHADAP WAJIB PAJAK ORANG PRIBADI YANG TERDAFTAR DI KANTOR PELAYANAN PAJAK PRATAMA MANADO - Parengkuan, Angelika Parengkuan; Ilat, Ventje; Warongan, Jessy D. L (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This study aims to determine and analyze the effect of perceived tax benefits, tax socialization, tax morals and knowledge of taxation on tax avoidance behavior. This type of research is quantitative research. The population in this study are individual taxpayers registered at the Manado Pratama Tax Service Office. The sampling technique in this study was purposive sampling technique and obtained a sample of 70 respondents. The data collection method used a questionnaire using multiple regression data analysis with the help of SPSS version 22. The results showed that the variables of Tax Benefit Perception (X1), Tax Socialization (X2), Tax Moral-Ethics (X3) and Tax Knowledge had an effect on taxpayers for do not do Tax Avoidance.